Docetaxel-Loaded Novel Nano-Platform for Synergistic Therapy of Non-Small Cell Lung Cancer - Feng, Xing; Xiong, Xiaoling; Ma, Shenglin (Frontiers in Pharmacology, 2022)
Today, non-small cell lung cancer (NSCLC) is threating the health of the whole people, and the current treatments are only marginally effective. So, the more low toxicity and efficient treatments are in sore need. In this paper, the smart nanoplat based on photothermal therapy, chemotherapy, and immunotherapy was constructed. The nanoparticles are composed of a novel photothermal agents, Mn-modified phthalocyanine derivative (MnIIIPC), docetaxel (DTX) and the effective targeting molecules, hyaluronic acid. The nano-platform could release the Mn2+ from MnIIIPC to activate tumor immunity through cGAS-STING and chemotherapy, respectively; furtherly, DTX was released in the process for removal of tumor cells. The "one-for-all" nanomaterial may shed some light on treating NSCLC in multiple methods.